TEATER DULMULUK: SEJARAH PERKEMBANGAN DAN PERANANNYA DALAM IDENTITAS BUDAYA PALEMBANG - Tiara Salsabila; Farida R Wargadalem; Helen Susanti (CARITA: Jurnal Sejarah dan Budaya, 2025)
This article explores in detail the existence and significance of Dulmuluk Theater as a unique cultural heritage of Palembang, carrying important historical, social, and cultural meanings. Using a literature review method, the author traces the origins of Dulmuluk, its evolution from traditional poetry recitations into a complete folk theater performance enriched with artistic and cultural symbols. The article also discusses the main elements of Dulmuluk performances, such as plot structure, characterization, and themes, as well as how this art form functions as a means to communicate moral messages, social critique, and preserve local values passed down through generations. The findings highlight that Dulmuluk is more than just a traditional entertainment; it is a cultural identity that strengthens the pride of Palembang society. The recognition from the government and international institutions like UNESCO underscores the importance of ongoing efforts to preserve and develop this art form so that it remains relevant in the modern era. The article emphasizes that continuous support from the community and government is essential to ensure that Dulmuluk remains a living heritage, passed on to future generations as part of Indonesia’s rich cultural patrimony.